ECOLOGICAL AND GEOGRAPHICAL BASIS FOR THE ORGANIZATION OF TRANSBOUNDARY PROTECTED NATURAL AREAS (Scientific journal of the Fergana State University, 2024)
Scientific works substantiate the possibilities of obtaining greater economic benefits through the creation of protected natural areas in border areas and their use for various purposes. Therefore, the article examines the possibility of creating protected natural areas in the border regions of the Republic of Uzbekistan using the example of the Fergana region. The possibilities of forming a system of transboundary protected natural areas in the border regions of the Fergana region in interaction with neighboring countries and their sustainable use in the future were also geographically analyzed. In this regard, proposals and recommendations have been developed for identifying rare natural objects and territories that are important for the conservation of biological and landscape diversity in the border zones of the Fergana region, and assigning them the status of transboundary protected natural areas.